Uji Diagnostik Dan Analisis Multivariat Prediktor Skor Glasgow Outcome Scale (GOS) pada Cedera Kepala Traumatik - Rabiva, Elmaeda; Pitra, Dian Ayu Hamama; Efriza, Efriza (Universitas Malahayati, 2025)
ABSTRACT Traumatic head injury is an injury that results in impaired brain function with high morbidity and mortality rates. Early patient outcome assessment plays an important role in clinical decision-making, resource allocation, and communication between clinicians and patients' families. Outcome in traumatic head injury patients is influenced by several interrelated predictors. This study was aimed to analyze variables (patient characteristics, Rotterdam score, Helsinki score, and Glial Fibrillary Acidic Protein (GFAP) levels) that may act as predictors of outcome in traumatic head injury patients. This study used an observational analytic design with a cross-sectional approach. Data collection was carried out prospectively in the medical record installation of RSUP Dr. M. Djamil Padang and the Biomedical Laboratory of Andalas University. From the results of bivariate analysis, the variables of age, Glasgow Coma Scale (GCS) score, Rotterdam score, and Helsinki score have a significant relationship with the value of the Glasgow Outcome Scale (GOS) score. The higher the age, the lower the GCS score, and the large number of rotterdam and helsinki scores indicate a higher risk of patients experiencing poor outcomes. From multivariate analysis, the most significant variable was GCS score with a p value of 0.00.Conclusion: Variables that have an association with GOS score are age, GCS score, Rotterdam score, and Helsinki score. The most significant variable is GCS score. Keywords: GCS, GFAP, GOS, Helsinki Score, Rotterdam Score, Traumatic Head Injury. ABSTRAK Cedera kepala traumatik adalah cedera yang mengakibatkan kerusakan otak dengan angka morbiditas dan mortalitas yang tinggi. Penilaian outcome dini pada pasien berperan penting dalam pengambilan keputusan klinis, pengalokasian sumber daya, dan komunikasi antara dokter dan keluarga pasien. Outcome pada pasien cedera kepala traumatik dipengaruhi oleh sejumlah prediktor yang saling mempengaruhi. Penelitian ini bertujuan untuk menganalisis variabel- variabel (karakteristik pasien, skor Rotterdam, skor Helsinki, dan kadar Glial Fibrillary Acidic Protein (GFAP) yang dapat berperan sebagai prediktor outcome pasien cedera kepala traumatik. Studi ini menggunakan desain analitik observasional dengan pendekatan cross-sectional. Data dikumpulkan secara prospektif di Instalasi rekam medis RSUP Dr. M. Djamil Padang dan Laboratorium Biomedik Universitas Andalas. Dari hasil analisis bivariat variabel usia, skor Glasgow Coma Scale (GCS), skor Rotterdam, dan skor Helsinki memiliki hubungan yang bermakna dengan nilai skor Glasgow Outcome Scale (GOS). Semakin tinggi usia, skor GCS yang rendah, serta jumlah skor rotterdam dan helsinki yang besar menunjukkan risiko pasien mengalami outcome buruk lebih tinggi. Dari analisis multivariat didapatkan variabel yang paling bermakna adalah skor GCS dengan nilai p value 0,00. Variabel yang memiliki hubungan dengan skor GOS adalah usia, skor GCS, skor Rotterdam, dan skor Helsinki. Variabel yang paling bermakna adalah skor GCS. Kata Kunci: Cedera Kepala Traumatik, GCS, GFAP, GOS, Skor Helsinki, Skor Rotterdam.